The Impact of Low Impact Aerobic Gymnastics on Body Mass Index and Thigh Circumference - Andi Fepriyanto; Dian Helaprahara; Ainur Rasyid (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
The purpose of the study was to examine the low impact aerobic gymnastics on body mass index and thigh circumference in women. The subjects of the study were 20 female members of Dharmawanita receiving low impact aerobic for 6 weeks. This study used an experimental method. Pre-test data were taken before the treatment and post-test data were taken after treatments. The data were then analyzed. The result showed the t-value was 6,26 for body mass index and 2.57 for thigh circumference, while t-table is 1.729 (p 0.05). It concludes that taking the low impact aerobic gymnastics can significantly reduce the body mass index and thigh circumference in women gradually.